2007
DOI: 10.1007/s11746-007-1064-2
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Granular Crystals in Margarine with Excess Amount of Palm Oil

Abstract: Crystallization behavior of palm oil and tripalmitin (PPP) in a model margarine system was investigated. The model margarine was held in a programmable oven, heated to 5°C for 12 h and then 20°C for a further 12 h. After 3 weeks, the model margarine was evaluated by polarization microscopy. Granular crystals were observed in the margarine containing an excess amount of palm oil and PPP. The concentration of higher-melting fatty acids was higher in the crystals relative to the surroundings. Likewise, the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 13 publications
1
60
0
1
Order By: Relevance
“…The high concentration of PPP species can favor the formation of POP, POSt, and SOS crystals, which are dense crystals with a high melting point. [2,24] The fraction of the intermediate melting point, represented by the symmetric disaturated species (SUS), is about 40.05%, consisting of MOP, POP, PLP, and POS. The symmetry of this group of TAGs is verified using regiospecific distribution analysis, as shown in Table 1, wherein approximately 72% of the saturated FAs are in the sn-1,3 position.…”
Section: Tag Composition and Regiospecific Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high concentration of PPP species can favor the formation of POP, POSt, and SOS crystals, which are dense crystals with a high melting point. [2,24] The fraction of the intermediate melting point, represented by the symmetric disaturated species (SUS), is about 40.05%, consisting of MOP, POP, PLP, and POS. The symmetry of this group of TAGs is verified using regiospecific distribution analysis, as shown in Table 1, wherein approximately 72% of the saturated FAs are in the sn-1,3 position.…”
Section: Tag Composition and Regiospecific Distributionmentioning
confidence: 99%
“…[1] Therefore, depending on the processing conditions and storage, PO has the potential to change the crystalline behavior of the product (i.e., β′ → β). [2] In this context, ensuring the stability of the β′ polymorph in PO-based products is of special interest for industry, because of the great economic importance associated with the use of this raw material. [3] It is known that adding foreign materials (referred to as templates or additives) in the crystallizing liquid is widely applied to modify the crystallization behavior of inorganic and organic substances, including fat crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Saadi et al 13 examined PO/PS blends and found that the PPO/POP content of the blends increased progressively as the level of PS increased. In another study, Tanaka et al 42 reported that POP, SOS or SSS are the components of the growing crystals in margarines prepared from palm oil and soybean oil although PPP will be the first to crystallize to form a granular crystal. Since MoO/PS blends shows the presence of all these TAGs, it can be considered suitable to be used as a fat stock for margarine formulation.…”
Section: Fa Compositionmentioning
confidence: 99%
“…Many studies were conducted to clarify the mechanism of granular crystal formation in palm oil-based products. They have suggested the possibility of a relationship between the transformation to the β-form and the formation of granular crystals in margarine (Ishikawa et al, 1980, Watanabe et al, 1992, Miura and Konishi, 2001, Sato 2001, Walstra et al, 2001, Tanaka et al, 2007, Tanaka et al, 2009. Information on crystallization behavior, including the polymorphic transition, is therefore important for the fat food industry.…”
Section: Introductionmentioning
confidence: 99%